OVEREXPRESSION OF Gα GENE INCREASES GROWTH AND HYPOSALINE TOLERANCE IN Kappaphycus alvarezii TRANSGENIC PLANTLETS - Erina Sulistiani (SEAMEO BIOTROP, 2021)
G proteins are membrane proteins that play roles in signal transduction in living organisms. They consist of α, β and γ subunits. The G protein α subunit (Gα) plays a role in plant resistance toward biotic and abiotic environmental stresses. Transgenic plantlets of Kappaphycus alvarezii carrying the Gα gene (derived from soybean) have been successfully obtained through Agrobacterium tumefaciens-mediated transformation. The present study aimed to: 1. compare the growth of non-transgenic and transgenic plantlets of K. alvarezii in vitro using Provasoli enriched seawater (PES) medium with normal salinity and hyposalinity and 2. analyze the expression level of the Gα gene in transgenic plantlets using quantitative Polymerase Chain Reaction (qPCR). The results showed that all transgenic plantlets (six clones) had significantly higher daily growth rate (DGR, % / d) than that of non-transgenic under the condition of normal salinity (30 ppt) and hyposalinity (15 and 20 ppt) for 5 weeks of observation. At 15 ppt, transgenic plantlets were more tolerant than non-transgenic ones, as most thalli of transgenic plantlets remained brown in color, whereas most thalli of non-transgenic plantlets were bleached. The results of the qPCR analysis showed that the expression of the Gα gene in transgenic plantlets increased by 6.43 - 8.03 times compared with that of non-transgenic plantlets. The result of Pearson correlation analysis showed that relative expression of Gα gene had a strong correlation, both with DGRs in normal salinity and hyposalinity of transgenic plantlets (correlation coefficient > 0.7). The correlation was linearly positive, where increased expression of the Gα gene was strongly associated with an increase in DGRs.